ADDRESSING ANTERIOR CROWDING OF THE LOWER JAW WITHOUT EXPANSION SCREWS - Irsyad, Widya; S Darwis, Rudi; Mulistira Prana, Annisa (Journal of Health and Dental Sciences, 2025)
Tooth malposition is a condition in which teeth are not in an ideal position in the jaw. Crowding and diastema are the most common malocclusion conditions encountered because of a mismatch between the length of the dental arch and jaw arch. Mild cases of malposition can be treated with removable orthodontic appliances. This report presents a case of anterior crowding of the lower jaw and the persistence of teeth 75 and 85. Removable orthodontic appliances were used to resolve anterior crowding without using expansion screws to gain space in the lower jaw. The removable orthodontic appliances used were coils and c-rectors as active components, and Adam's hooks to gain retention. Labial bows were used to maintain the shape of the dental arches. In the upper jaw, a central diastema caused by an abnormal frenulum attachment was observed. After 9 months of treatment, the anterior crowding of the lower jaw improved by utilizing the space which was the difference in width between teeth 75 and 85, and teeth 35 and 45, which replaced their positions. . Patient cooperation in the use of removable orthodontic appliances to obtain good treatment results can be achieved by consistently educating and remotivating patients. DOI : 10.54052/jhds.v5n1.p79-88